ON THE BEHAVIOR OF MARINE CRUSTACEANS IN AN ELECTRICAL FIELD OF ALTERNATING CURRENT - BISWAS, K P (Fishery Technology, 2025)
The minimum flow of current essential to produce electronarQ cosis and fixation in marine crustaceans, Metapenaeus affinis1 Parapenaeopsis styli(era1 Panulirus ornatus and Neptunus sanguinofentus in an AC field of specific strength varied with the lengths of animals tested, except in case of the last one where the increase in size of animals showed no significant effect on the effective period for different reactions. M. affinis in interrupted AC required threshold pulses for narcosis and fixation, which varied inversely with the length of the organism. Animals mbjected to current of higher effective period required Ion ger time for recovery in interrupted AC of 50 cfs. The period for narcosis and recovery of M. af(tnis did not vary significantly with repeated stimulations on the same organism